Effects of stocking density and photoperiod manipulation in relation to estradiol profile to enhance spawning activity in female Nile tilapia - Edward E. Onumah; Stephan Wessels; Nina Wildenhayn; Gabriele Hoerstgen-Schwark; Bernhard Brümmer (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2009)
This study investigated the effects of stocking density and photoperiod manipulation in relation to plasma estradiol-17? (E2) profile to enhance spawning activity in female Nile tilapia (Oreochromis niloticus) using F1 clonal crosses. The fish were divided into experimental and control groups and subjected to a combination of stocking density and photoperiod treatments (40kg/m3;6L:18D, 40kg/m3;12L:12D and transferred into single compartments at 12L:12D; 14kg/m3;12L:12D), respectively. Blood samples were taken by caudal puncture from experimental fish for estradiol profile analysis. Results showed that experimental fish exhibited significantly higher number of spawns per day, total fecundity and relative fecundity (p<0.05). Hatching and swim-up rates were also higher in the experimental than in the control group. Regression analysis revealed a significant positive relationship between fish size (body weight), total and relative fecundity (p<0.001). However, the relationship between fecundity and inter-spawning interval (ISI) and between ISI and fish weight were weak and insignificant. It was also revealed that E2 levels demonstrated a pattern based on completed reproductive cycle. The study therefore established that a combination of stocking density and photoperiod treatments can be adopted to manipulate the timing of spawning activity in female Nile tilapia without having adverse effect on other reproductive parameters such as egg qualities and fecundity. Findings further suggested that the effects of exogenous factors on manipulation of spawning activities of female Nile tilapia are achieved as a result of hormonal changes including E2 levels.
Keywords: 630; Stocking density; Photoperiod; Spawning; Estradiol levels; Nile tilapia